2021
DOI: 10.1136/jclinpath-2021-208034
|View full text |Cite
|
Sign up to set email alerts
|

Biomarker testing strategies in non-small cell lung cancer in the real-world setting: analysis of methods in the Prospective Central Lung Cancer Biomarker Registry (LungPath) from the Spanish Society of Pathology (SEAP)

Abstract: AimsThe aim of this study is to extend the analysis of the Lung Cancer Biomarker Testing Registry (LungPath), by analysing the techniques used in the determination of epidermal growth factor receptor (EGFR), anaplastic lymphoma kinase (ALK), c-ros oncogene 1 (ROS1) and programmed death ligand-1 (PD-L1) for the diagnostic of patients with advanced non-small-cell lung cancer (NSCLC).MethodsInformation of the technique used for the determination of EGFR, ALK, ROS1 and PD-L1 was recorded from March 2018 to January… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Although ROS1 was negative on immunohistochemistry in our case, international guidelines recommend immunohistochemistry (IHC) as a screening method for ROS1 fusions in lung cancer 19 and this technique is usually highly concordant and less expensive than FISH. Confirmation of positive cases is recommended by a cytogenetic or molecular method.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although ROS1 was negative on immunohistochemistry in our case, international guidelines recommend immunohistochemistry (IHC) as a screening method for ROS1 fusions in lung cancer 19 and this technique is usually highly concordant and less expensive than FISH. Confirmation of positive cases is recommended by a cytogenetic or molecular method.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, it is important to consider that ROS1 expression without underlying rearrangement (false positives) has been described in almost one-third of tumors. 19 In gliomas, although ROS1 rearrangements can be detected by FISH, GOPC::ROS1 fusions can be difficult to detect by FISH analysis because both genes are closely located on 6q22.1 and require a specifically designed probe set to detect them. 20 Therefore, the use of molecular techniques to detect such alterations is justified.…”
Section: Discussionmentioning
confidence: 99%
“…NGS is a technology that requires a level of expertise that most of pathologists do not possess. A recent Spanish publication showed that IHC and FISH remain the most widely used techniques compared to NGS, with only 1 out of 44 centers using the latter [31].…”
Section: Discussionmentioning
confidence: 99%
“…As part of precision oncology, NGS is a technology that can allow integration of molecular tumor profiles into clinical decision‐making and have increasingly replaced conventional techniques 12,13 . However, an analysis of methods in the Central Prospective Registry of Lung Cancer Biomarkers (LungPath) of the Spanish Society of Anatomic Pathology (SEAP) showed that the level of implementation of NGS was still low and mainly single‐gene conventional tests 14,15 . In an approach recently suggested by ESMO, it will increasingly become necessary to deploy multigene testing with NGS‐based techniques for the genomic profiling of cancer 9,16 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, an analysis of methods in the Central Prospective Registry of Lung Cancer Biomarkers (LungPath) of the Spanish Society of Anatomic Pathology (SEAP) showed that the level of implementation of NGS was still low and mainly single-gene conventional tests. 14,15 In an approach recently suggested by ESMO, it will increasingly become necessary to deploy multigene testing with NGS-based techniques for the genomic profiling of cancer. 9,16 However, such support does not necessarily translate to equitable access to NGS within and across countries due to gaps in its implementation: varying practices in its use and access, which demonstrates different degrees of efficiency and deficiency across each European country.…”
Section: Introductionmentioning
confidence: 99%